2018
DOI: 10.3233/jad-180140
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of Plasma Amyloid-β Level is More Significant in Early Stage of Cognitive Impairment: A Population-Based Cross-Sectional Study

Abstract: Levels of plasma Aβ42 and Aβ42/Aβ40 ratio were elevated in patients with possible cognitive impairment, indicating that plasma Aβ42 and Aβ42/Aβ40 ratio increases may be more pronounced in early stage of cognitive impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 45 publications
2
13
0
Order By: Relevance
“…Sophisticated methods for A␤ analysis have been developed in recent years, but results from the first diagnostic and epidemiological applications of these methods have been inconsistent. A number of studies have found an association of lower plasma A␤ concentrations (thought to reflect a greater brain A␤ burden) with more severe neuropsychological deficits [23,24], with an increased risk of developing AD [25,26], and with amyloidpositive PET [8,27,28] or amyloid-abnormal CSF [29,30] as current gold standards for AD diagnosis. Others report results in the opposite direction [31][32][33][34] and null findings, too, are frequent [35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Sophisticated methods for A␤ analysis have been developed in recent years, but results from the first diagnostic and epidemiological applications of these methods have been inconsistent. A number of studies have found an association of lower plasma A␤ concentrations (thought to reflect a greater brain A␤ burden) with more severe neuropsychological deficits [23,24], with an increased risk of developing AD [25,26], and with amyloidpositive PET [8,27,28] or amyloid-abnormal CSF [29,30] as current gold standards for AD diagnosis. Others report results in the opposite direction [31][32][33][34] and null findings, too, are frequent [35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with our findings, large population-based studies have reported the association of increased Aβ40 with the risk of dementia as well as with declining cognitive measurements (Hilal et al, 2018;Verberk et al, 2018); however, some studies also found an association between plasma Aβ42 and impaired cognition (Llado-Saz et al, 2015). Differences in patient age, clinical status, and analysis techniques may affect plasma Aβ quantification and result in inconsistencies between studies (Toledo et al, 2013;Palmqvist et al, 2018;Wang et al, 2018). We further found an association between the STT-A and AVLT-R scores, and the average FA values within the regions exhibit significant group differences, indicating that plasma Aβ40-related WM structural changes may reflect cognitive function in individuals with SCD.…”
Section: Discussionsupporting
confidence: 83%
“…The lifestyle and population composition of the village are similar to other rural areas in Xi'an. This cluster sampling method is consistent with statistical rules and has been proved to be reliable in our previous publications (Wang et al, 2018). The inclusion criteria were the following: (1) age 45 years or older, (2) registered permanent resident living in Qubao Village for more than 3 years, and (3) consented to participate in the study.…”
Section: Study Populationmentioning
confidence: 89%
“…Fasting blood samples (8:00-9:00 AM) were collected into vacutainers containing EDTA, an anticoagulant, centrifuged at 3000 g for 10 min, and stored at -80 • C until use. Plasma Aβ 1-40 and Aβ 1-42 levels were measured with sandwich enzyme-linked immunosorbent assay kits (ELISA, Yuanye Co., Shanghai, China) as previously described (Wang et al, 2018). Measurements were performed by professionals in an independent laboratory of neurology.…”
Section: Detection Of Plasma β-Amyloid Levelsmentioning
confidence: 99%